KAPABILITAS PEMASARAN, PEMASARAN KEWIRAUSAHAAN, KINERJA PEMASARAN PADA UKM DI INDUSTRI EKONOMI KREATIF PONTIANAK - Arweni, Arweni (Jurusan Akuntansi Politeknik Negeri Pontianak, 2024)
The creative economy industry has an important role in a country's economic growth, as it focuses on the creation of products and services based on creativity and expertise. As one of the developing cities in Indonesia, Pontianak must identify its creative industry potential. With the lack of natural resources, creative industries can be the best alternative to boost the city's economic growth. Small and medium enterprises, also known as SMEs, play an important role in economic expansion. The purpose of this study was to determine the marketing performance, entrepreneurial marketing, and marketing capabilities of SMEs in Pontianak in the creative economy sector. SMEs in Pontianak's Creative Economy Industry constitute the research population. Sampling will use simple random sampling, to get a sample of this research will use Hair's theory, so that a sample of 237 respondents is obtained. Using the WarpPLS analysis tool, multiple linear regression analysis is the data analysis method used in this study. This investigation shows that the available data supports all the hypotheses proposed, namely that entrepreneurial marketing characteristics and marketing capacity both affect marketing performance.